CCNA collaboration 210-065 CIVND official cert guide - Morgan, Brian (Brian Edward); Ball, Jason (Cisco Press, 2016)
CCNA Collaboration CIVND 210-065 Official Cert Guide CCNA Collaboration CIVND 210-065 Official Cert Guide from Cisco Press enables you to succeed on the exam the first time and is the only self-study resource approved by Cisco. Expert Cisco Collaboration engineers Brian Morgan and Jason Ball share preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. This complete, official study package includes A test-preparation routine proven to help you pass the exam "Do I Know This Already?" quizzes, which enable you to decide how much time you need to spend on each section Chapter-ending exercises, which help you drill on key concepts you must know thoroughly The powerful Pearson IT Certification Practice Test software, complete with hundreds of well-reviewed, exam-realistic questions, customization options, and detailed performance reports A final preparation chapter, which guides you through tools and resources to help you craft your review and test-taking strategies Study plan suggestions and templates to help you organize and optimize your study time Well regarded for its level of detail, study plans, assessment features, challenging review questions and exercises, this official study guide helps you master the concepts and techniques that ensure your exam success. CCNA Collaboration CIVND 201-065 Official Cert Guide is part of a recommended learning path from Cisco that includes simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press. To find out more about instructor-led training, e-learning, and hands-on instruction offered by authorized Cisco Learning Partners worldwide, please visit www.cisco.com. The official study guide helps you master topics on the CCNA Collaboration CIVND 210-065 exam, including the following: Cisco Collaboration components and architecture Cisco Digital Media Suite, Digital Signs, Cisco Cast, and Show and Share Cisco video surveillance components and architectures Cisco IP Phones, desktop units, and Cisco Jabber Cisco TelePresence endpoint portfolio Cisco Edge Architecture including Expressway Multipoint, multisite, and multiway video conferencing features Cisco TelePresence MCU hardware and server family Cisco TelePresence management Cisco WebEx solutions The CD-ROM contains more than 140 practice questions for the exam, memory table exercises and answer keys, and a study planner tool. Includes Exclusive Offer for 70% Off Premium Edition eBook and Practice Test Pearson IT Certification Practice Test minimum system requirements: Windows 10, Windows 8.1, Windows 7, or Vista (SP2), Microsoft .NET Framework 4.5 Client; Pentium-class 1 GHz processor (or equivalent); 512 MB RAM; 650 MB disk space plus 50 MB for each downloaded practice exam; access to the Internet to register and download exam databases This volume is part of the Official Cert Guide series from Cisco Press. Books in this series provide officially developed exam preparation materials that offer assessment, review, and practice to help Cisco Career Certification candidates identify weaknesses, concentrate their study efforts, and enhance their confidence as exam day nears. Register your product at ciscopress.com/register for convenient access to downloads, updates, and corrections as they become available.